Link maps and map meetings: Scaffolding student learning - Christine Lindstrøm; Manjula D. Sharma (Physical Review Special Topics. Physics Education Research, 2009)
With student numbers decreasing and traditional teaching methods having been found inefficient, it is widely accepted that alternative teaching methods need to be explored in tertiary physics education. In 2006 a different teaching environment was offered to 244 first year students with little or no prior formal instruction in physics. Students were invited to attend additional enrichment classes 1 h a week called map meetings. The focus of these classes was a different type of visual presentation of physics material called link maps. Link maps explicitly show the key concepts covered in lectures and how these interrelate to help novices establish their physics schemata. In each map meeting the link map for the different topic was interactively discussed by the researcher before the students worked on problems in groups using the link map. The class ended with the researcher going through one problem, talking aloud about how to logically attack it. The results were promising. Each week about 20% of the class voluntarily attended map meetings whereas 22% reported that they did not attend due to timetable clashes. Two questionnaires revealed that students thought the classes were helpful for gaining an overview of physics and for developing their problem solving abilities. In the final examination the 32 students who had attended at least eight out of ten map meetings achieved, on average, 9 points out of 90 better in the examination (p=0.004) than a comparison group (N=40) with similar academic background which had not attended map meetings. The results of this study suggest that map meetings are a valuable learning environment for physics novices. Further investigations are currently being undertaken.